Beta-thalassemia in Mediterranean countries. Findings and outlook - Gil Bellis; Alain Parant (Investigaciones Geográficas)
Beta-thalassemia is one of the most common genetic disorders among humans. It occurs in many world regions, but the highest levels are recorded in the Mediterranean countries. This study reviews the epidemiology of β-thalassemia in these countries, as well as their resources for fighting the disease, and establishes an outlook on the trends in the pathology between now and 2050. The epidemiological parameters are based on information from specialised databases, while the outlook is derived from the global population forecasts of the United Nations. With an incidence rate at birth of 15.9 cases per 100,000 newborns, the Northern coast of the Mediterranean is the least impacted and has significant health infrastructures; the number of newborns concerned could decrease by 2050. The incidence rate on the Eastern Mediterranean coast, where numerous prevention programmes are available, is twice as high, at 31.4 per 100,000 newborns; over the next 30 years, the number of new cases at birth could increase. The incidence rate on the Southern Mediterranean coast is highest, at 36.8 per 100,000 newborns, and the region continues to suffer from a shortage of health infrastructures; the number of new cases at birth could increase considerably in the region between now and 2050. These long-term projections are based on population growth in the Mediterranean countries and will be changed only by the widespread use of antenatal practices against β-thalassemia. The findings of this study could enable the countries concerned to adapt their healthcare policies.